Outcomes of direct-acting antivirals in patients with HCV decompensated cirrhosis: a systematic review and meta-analysis - Jongraksak, Tanawat; Chuncharunee, Alan; Intaraprasong, Pongphob; Tansawet, Amarit; Thakkinstian, Ammarin; Sobhonslidsuk, Abhasnee (Frontiers in Medicine, 2023)
Background: Direct-acting antivirals (DAA) are effective for chronic hepatitis C virus (HCV) treatment. However, their impact on overall survival (OS), hepatocellular carcinoma (HCC) occurrence, HCC-free survival, and liver function in patients with HCV decompensated cirrhosis remains uncertain. This study aimed to evaluate the effects of DAA treatment on this population.Methods: Studies were identified by searching the MEDLINE, SCOPUS, and CENTRAL databases. OS and HCC-free survival probabilities and time data were extracted from Kaplan-Meier curves. A one-stage meta-analysis using parametric Weibull regression was conducted to estimate the relative treatment effects of DAA versus no DAA. The primary outcome was the OS rate. The secondary outcomes were HCC-free survival, HCC occurrence rate, and improvement in the Model for Endstage Liver Disease (MELD) score.Results: Eight cohorts comprising 3,430 participants (2,603 in the DAA group and 1,999 in the no-DAA group) were included. The OS probabilities at 12 and 24 months were 95% and 90% for the DAA group, respectively, compared with 89% and 80% in the no-DAA group, respectively. Hazard ratio (HR) was 0.48 (95% confidence interval (CI):0.39, 0.60; p < 0.001). The HCC-free survival probabilities at 12 and 24 months were 96% and 90%, respectively, in the former, and 94% and 85%, respectively, in the latter. The HR of HCC occurrence was 0.72 (95%CI:0.52, 1.00; p=0.05), which suggests that DAA treatment in decompensated cirrhosis may lead to a 28% lower risk of HCC occurrence. The mean MELD score difference was -7.75 (95% CI: -14.52, -0.98; p = 0.02).Conclusions: Improvement in OS and MELD score is a long-term benefit of DAA treatment in patients with HCV decompensated cirrhosis, with a marginal effect of the treatment on HCC development.